The Responsibilities of Business Actors and The Legal Implications of Minors Purchasing Online Mobile Game Credits - Indradewi, Astrid Athina; Siswanto, Carissa Amanda; Haryono, Leonardo Caesar (Universitas Serang Raya, 2024)
Children’s interactions and lifestyles worldwide have greatly benefited from the expansion of the internet gaming sector. However, the practice of minors purchasing and reselling online game certificates has prompted concerns about the accountability of corporate operators and potential legal repercussions. In the context of minors purchasing online game vouchers, this study investigates the responsibilities of commercial actors and the legal implications. This research methodology uses a normative legal approach to gather data from the literature, relevant judicial judgments, statutes, and regulations. This analysis aims to comprehend corporate actors' accountability, legal ramifications, and parents' function in this type of transaction. The findings demonstrated that business actors who offer online game vouchers have a duty to uphold the legitimacy of transactions. Businesses have a responsibility to make sure that such transactions adhere to ethical and legal standards, even though many laws forbid minors from engaging in transactions without their parent's permission. The legal ramifications of minors purchasing and selling online game vouchers may include possible violations of consumer rights, the protection of personal data, and provisions of contracts that may be void owing to age restrictions. Monitoring and limiting their children's access to these kinds of transactions is a crucial responsibility for parents. Collaboration between commercial actors, the government, and parents is required to maintain the integrity and protection of children in online game voucher purchasing and selling operations.